2000
DOI: 10.1177/016555150002600105
|View full text |Cite
|
Sign up to set email alerts
|

Information communication networking in rural communities: the case of women in Imo State, Nigeria

Abstract: This research focuses on exploring the existence or otherwise of any interactive information communication networks among women in Imo State. Using questionnaire and oral interview techniques, data were collected from 600 women, purposively chosen, covering the three senatorial zones of the State. Results show the existence of vibrant interactive networks among women, carried out on two levels: (i) diffused or non-restrictive patterns and (ii) restrictive or discriminatory patterns. Social, economic, political… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…According to Tella et al [42], quoting Akintoye [43], money remains the most significant motivational strategy. For example, Frederick Taylor, and his scientific management associates described money as the most important factor in motivating the industrial workers to achieve greater productivity.…”
Section: Ajegbomogun and So Popoola / Motivational Strategies Andmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Tella et al [42], quoting Akintoye [43], money remains the most significant motivational strategy. For example, Frederick Taylor, and his scientific management associates described money as the most important factor in motivating the industrial workers to achieve greater productivity.…”
Section: Ajegbomogun and So Popoola / Motivational Strategies Andmentioning
confidence: 99%
“…The United States military used it for the fast dissemination of information. Today, it is the most sophisticated and modern way of interactive networking and offers global access to many kinds of information generation and sharing across the world, thus reducing the world to a "global village" [43].…”
Section: Introductionmentioning
confidence: 99%
“…Another part of the status problem is women's secretiveness, being too often unwilling to interact with one another and share information. This more often than not fuels ignorance, misunderstanding, fear, rumour and gossip (Uhegbu, 2000).…”
Section: Status Of Rural Women In Nigeriamentioning
confidence: 99%
“…This situation could be a result of what Nwokocha and Uhegbu (2000) deem to be the use of inappropriate channels of information dissemination which do not ensure accessibility to HIV/AIDS information. Research by Uhegbu (2000) has shown that the mass media are not easily accessible to many rural Nigerians due to factors such as poverty and illiteracy. The solution to combating the continued HIV/AIDS ignorance of the rural women therefore lies in adopting more accessible, convenient, familiar and cost-effective dissemination methods which could usher in a new understanding and appreciation of the reality of HIV/AIDS in Nigeria.…”
Section: Dissemination Of Hiv/aids Informationmentioning
confidence: 99%